Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Dan Kinerja Tenaga Kesehatan - Oka Suryadinatha Gorda, Ayu Eka Aryawati Mariani, (Jurnal Ekonomi, 2019)
Leadership in the workplace is inseparable from spiritual values; therefore, it is very important to instill spiritual moral values for all employees. Nurses and midwives as part of human resources must have high performance and job satisfaction in order to support the achievement of the stated goals by the hospital. This study aims to determine the effect of spiritual leadership, employee engagement, work motivation, and job satisfaction on the performance of health workers in Dharma Yadnya Hospital. This study uses a quantitative approach. The scope of this study is identified as all the employees of Dharma Yadnya Hospital with the sample are 65 respondents. Data was collected by using questionnaires and processed with Partial Least Square (PLS) software. The results of this study showed that spiritual leadership, employee engagement, work motivation have significant effect on the performance and job satisfaction of health workers.